Roles of Phase Purity and Crystallinity on Chloramphenicol Sensing Performance of CuCo2O4/CuFe2O4-based Electrochemical Nanosensors. Issue 2 (3rd February 2021) - Pham, Tuyet Nhung; Van Cuong, Nguyen; Dinh, Ngo Xuan; Van Tuan, Hoang; Phan, Vu Ngoc; Thi Lan, Nguyen; Nam, Man Hoai; Thanh, Tran Dang; Lam, Vu Dinh; Van Quy, Nguyen; Huy, Tran Quang; Phan, Manh-Huong; et al.
Abstract : For the first time, the influences of phase purity and crystallinity on the electrochemical and electrocatalytic properties of CuCo2 O4 (CCO) and CuFe2 O4 (CFO)-based electrochemical sensors for the detection of chloramphenicol (CAP) are reported. A series of CCO and CFO nanoparticles were prepared by a modified coprecipitation method and then annealed at different temperatures under air (400 °C, 600 °C, 800 °C, and 1000 °C). Surface morphology, the evolution of the crystallite size, and crystalline phase transition, as well as phase purity of CCO and CFO at each annealing temperature, were characterized via different techniques. Their electrochemical properties were analyzed using cyclic voltammetry and differential pulse voltammetry measurements conducted with a PalmSens3 workstation. Results obtained show that the phase purity and crystallinity have decisive effects on their electrocatalytic activity, conductivity, and adsorption efficiency. Under an optimized condition (more namely, annealed 600 °C), both CCO and CFO samples offer high phase purity with low percent of CuO side phase (below 38%), small enough size with a large number of defects and available active sites; particularly, the cubic CFO nanoparticles are present due to its tetragonal phase transition. The modified electrodes with CCO-600 and CFO-600 exhibit a better voltammetric response, a higher synergistic electrocatalytic activity, and a greater electrochemical performance of comparing to other modified electrodes. They respond linearly to chloramphenicol (CAP) in the range from 2.5 to 50 μ M. Furthermore, they display am excellent long-term stability, reproducibility, and good selectivity, as well as their capacity of detecting CAP in the real milk sample.